2015
DOI: 10.1016/j.ces.2015.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pore coking in catalyst for thermal down-hole upgrading of heavy oil

Abstract: a b s t r a c tHeavy oil and bitumen are a potential alternative energy source to conventional light crude. However, recovery of these resources can have substantial environmental impact. Downhole upgrading offers the prospect of both improving recovery, and decreasing environmental impact. However, use of catalysts to enhance downhole upgrading is limited by the need for one that can survive the extreme coking conditions arising from the cracking of heavy oil. In this work the potential of hydrogen donors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Notably, upgrading with CH:oil ratio of 0.04 g·g −1 under nitrogen atmosphere had a similar effect to adding hydrogen. The results presented in Tables 5 and 6 show that the trend in the amount of coke and API gravity after upgrading is consistent with the report of Dim et al [18]. The slight increase in API gravity with increasing CH:oil ratio whilst suppressing coke formation suggests that significant carbon-rejection in the upgrading reaction is required for a remarkable API gravity rise.…”
Section: Api Gravity Viscosity and Asphaltenesupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, upgrading with CH:oil ratio of 0.04 g·g −1 under nitrogen atmosphere had a similar effect to adding hydrogen. The results presented in Tables 5 and 6 show that the trend in the amount of coke and API gravity after upgrading is consistent with the report of Dim et al [18]. The slight increase in API gravity with increasing CH:oil ratio whilst suppressing coke formation suggests that significant carbon-rejection in the upgrading reaction is required for a remarkable API gravity rise.…”
Section: Api Gravity Viscosity and Asphaltenesupporting
confidence: 90%
“…Hydrogen helps to stabilise generated free radicals that are formed during cracking reactions, to narrow the molecular weight distribution of the product. It has been reported that the dehydrogenation of cycloalkanes such as cyclohexane, methylecyclohexane, and decalin can provide an effective hydrogen supply to cap generated coke precursors during catalytic upgrading [16,18,20]. Dehydrogenation of cyclohexane (CH) could liberate hydrogen for hydrocracking and hydrogenation reactions, if the partial pressure of hydrogen is high enough.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISC method uses vertical producer wells except in the toe-to-heal air injection (THAI) variant which consists of a combination of direct or staggered vertical injection (into which air is injected at 600 to 700 °C) and horizontal producer wells [63]. Today, due to huge cost limitation and requirement of special operation conditions, only a few ISC operate.…”
Section: Overview Of the Methodsmentioning
confidence: 99%
“…Coke deposits could block the pore structures and active sites for oil conversion, and consequently, the catalyst could regain its utmost cracking activity via complete carbon removal. 43 Table 3 presents the pore properties of different FCC catalysts analyzed by N 2 -absorption. As anticipated because the original FCC catalyst had the most developed pore structures, the surface area of A-FCC catalyst substantially decreased during the hydrothermal treating process, also with slightly lower pore volume and larger pore diameter, which might be caused by the agglomeration of some tiny pores in the hot steam atmosphere.…”
Section: Energy and Fuelsmentioning
confidence: 99%